PELABUHAN BARU BATAVIA: TRANSFORMASI PELABUHAN TANJUNG PRIOK, 1883-1925 - Yusuf, Nur Fadilah (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2023)
The article provides a detailed account of the development of Tanjung Priok Port, from its establishment in 1883 to when it was equipped with a station in 1925. The port was built in response to the opening of the Suez Canal in Egypt, which significantly impacted the maritime development of Europe to the Far East, including the Dutch East Indies. The rapidly growing shipping activities, which relied on sea routes, could no longer be accommodated by the Sunda Kelapa Harbour. Consequently, the government decided to construct Tanjung Priok port. This study uses a historical method that includes heuristics, source criticism, interpretation, and historiography. The author discusses various aspects of Tanjung Priok Port, namely the construction process, the port's condition, development, and supporting elements. Additionally, the article covers the port activities before the formal institutional establishment of Tanjung Priok Port